THE EFFECT OF SOAKING CIPLUKAN LEAVES (Physalis angulata L.) EXTRACT TOWARDS AND CONTAINMENT PERIODS THE QUALITY OF CHICKEN EGGS AND DUCK EGGS - S. A., Sakila; Okarini, I. A.; Umiarti, A. T.; Sarini, N. P.; Wirapartha, I M. (Jurnal Peternakan Tropika, 2022)
Eggs are one of the post harvest products that are easily damaged and have a relatively short shelf life. Preservation is one way to extend the shelf life and maintain the functional properties of foodstuffs that are easily damaged. This study aims to determine the effect of immersion on the quality of chicken eggs and duck eggs in ciplukan leaves extract with different containment periods and the interaction between containment periods and the type of eggs soaked with ciplukan leaves extract. The total eggs used in this study were 48 eggs. This study used a completely randomized design with a factorial pattern, with two factors, namely  containment periods (15 days and 30 days) and the type of egg (chicken eggs and duck eggs). The variables observed were changes in egg weight, egg white index (IPT), egg pH and colour yolk. The data obtained were analyzed using analysis of variance (ANOVA) and continued with Duncan's multiple distance test at a 95% confidence level. The results of this study showed that the weight of eggs in the treatment of containment periods was significantly different (P<0.05), while in the treatment of egg types it was significantly different (P<0.05) on the egg white index (IPT) and egg pH.  Colour variable yolk indicates the results are not significantly different (P>0.05). Soaking chicken eggs and duck eggs in 6% ciplukan leaves extract for 12 hours had an effect on egg weight, egg white index (IPT) and egg pH during storage. There was no interaction between containment periods treatment and egg type in all variables. Key words: chicken eggs, duck eggs, ciplukan leaves, containment periods, eggs quality